OBSERVATIONS ON THE DISTRIBUTION AND FLUCTUATIONS OF PLANKTON IN THE HOOGHLY-MATLAH ESTUARINE SYSTEM, WITH NOTES ON THEIR RELATION TO COMMERCIAL FISH LANDINGS - Shetty, H P C; Saha, S B; Ghosh, B B (Indian Journal of Fisheries, 2011)
OBSERVATIONS'on the plankton of the Hooghly-Matlah estuarine systemwere taken up in order to study its distribution and seasonal fluctuations,as part of a comprehensive study on the commercially important fish populationsof the estuary. Some workers like Juday, Rich, Kemmerer and Mann(1932) and Ricker (1938) have attempted to relate fluctuations in planktonpopulations to the vital statistics of commercially important fishes. Thesignificance of plankton studies in elucidating some of the probable factorsresponsible for fluctuations in abundance and movements of fish stocks iswell known. The Hooghly-Matlah esttiarine system is of great economicimportance from the fisheries point of view and a detailed study of the planktonof this estuary is expected to throw some light on the pattern of fluctuationsin its fisheries.